Photoaging of human retinal pigment epithelium is accompanied by oxidative modifications of its eumelanin. (27th March 2013) - Ito, Shosuke; Pilat, Anna; Gerwat, Wolfram; Skumatz, Christine M. B.; Ito, Miho; Kiyono, Atsumi; Zadlo, Andrzej; Nakanishi, Yukiko; Kolbe, Ludger; Burke, Janice M.; Sarna, Tadeusz; Wakamatsu, Kazumasa
Summary Although photodegradation of the retinal pigment epithelium (RPE) melanin may contribute to the etiology of age‐related macular degeneration, the molecular mechanisms of this phenomenon and the structural changes of the modified melanin remain unknown. Recently, we found that the ratio of pyrrole‐2, 3, 4, 5‐tetracarboxylic acid (PTeCA) to pyrrole‐2, 3, 5‐tricarboxylic acid (PTCA) is a marker for the heat‐induced cross‐linking of eumelanin. In this study, we examined UVA‐induced changes in synthetic eumelanins to confirm the usefulness of the PTeCA/PTCA ratio as an indicator of photo‐oxidation and compared changes in various melanin markers and their ratios in human melanocytes exposed to UVA, in isolated bovine RPE melanosomes exposed to strong blue light and in human RPE cells from donors of various ages. The results indicate that the PTeCA/PTCA ratio is a sensitive marker for the oxidation of eumelanin exposed to UVA or blue light and that eumelanin and pheomelanin in human RPE cells undergo extensive structural modifications due to the life‐long exposure to blue light.